FLAT PLATE PULSATING HEAT PIPE FOR ELECTRONICS COOLING - Betancur Arboleda, Luis Alonso; Krambeck, Larissa; Guessi Domiciano, Kelvin; Zonta, Guilherme; Barbosa Henriques Mantelli, Marcia (Revista de Engenharia Térmica, 2024)
Pulsating heat pipes are simple passive devices with excellent heat transfer capabilities, presenting low thermal resistance. Its thermal performance is mainly influenced by the thermophysical properties and volume of the working fluid. In this context, the impact of ethanol on the thermal performance of a diffusion-bonded flat plate pulsating heat pipe, composed of round channels with lateral grooves in the evaporator, is experimentally studied in this research. The experimental results of the pulsating heat pipe are compared with a previous study using distilled water. The grooved flat plate pulsating heat pipe is specially designed for cooling large-scale electronics (208x150x4.4 mm3), including those for space applications. Its thermal behavior is investigated in three different orientations: gravity-assisted, horizontal and against-gravity. The device with ethanol works satisfactorily in all tested positions. The most notable impact of the ethanol was in the thermal enhancement of the PHP operating in the against-gravity orientation, reducing the thermal resistance and the evaporator temperature by 10 °C. Besides, ethanol promotes early startup in the horizontal and against-gravity positions. This research extends the operating range of the pulsating heat pipe for cooling large-scale electronics, enabling the device for future microgravity tests aboard a sounding rocket.